6x - 3 - 4 - 8x = x +2
Like Terms
-2x - 7 = x + 2
Add 7 on each side
-2x = x + 9
Subtract x on each side
-3x = 9
Divide by -3 on each side
x = -3
2006-11-14 07:50:04
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
You need to put all of the numbers that have X with them on one side, (6x, -8x, and x). The last x is just one x. You also have to change that last x to a negative x, because you're moving it tothe other side of the = sign....so you should have
6x - 8x - x
Then you move all of the other numbers to the other side of the = sign (-3, -4, and the 2). The -3 and the -4 change to + numbers because you're moving to the other side of the = sign, just like with the x's.
You should then have
6x - 8x -x = 2 + 3 + 4
Which would be:
-3x = 9
Then you can divide both sides by -3, so that you will have just an x
In this case,
x = -3
2006-11-14 15:46:35
·
answer #2
·
answered by Nancy 3
·
0⤊
0⤋
first you know that you cannot subtract in an equation like this, so let's change the signs.
6x + (-3) + (-4) + (-8x)= x + 2
now on the left let's group like groups together making sure we keep the sign in FRONT of that number together:
6x + (-8x) + (-3) + (-4) = x + 2
now we are ready to starting doing the functions for each set of numbers:
6x + (-8x) = (-2x)
(-3) + (-4) = (-7)
thus far your equation looks like this:
-2x + (-7) = x + 2 now let's start isolating the x's, remembering that x always has an understood or invisible 1 in front of it, also remember that what you do to one side you must do to the other when moving numbers/letters side to side.
-2x + (-7) = 1x +2
-1x -1x
__________________
-3x +(-7) = 2
now we can start moving the (-7) from left to right., if it is a positive number you subtract, in this case a negative number, so you add on each side.
-3x + (-7) = 2
(+7) +7
_____________
-3x = 9
now to get the x by itself we divide by (-3)
-3x= 9
_______
-3
answer x= -3
the reason the 3 is a negative is because when multiplying OR dividing (+) or (-) numbers, you count the (-) signs, if it is a even number of (-) signs the answer is positive, if an odd number of (-) signs.
for more great help go to www.purplemath.com
2006-11-14 16:01:36
·
answer #3
·
answered by trish the dish 3
·
0⤊
0⤋
6x - 3 - 4 - 8x = x + 2
-2x-7=x+2
-x=9
x=-9
2006-11-14 15:50:15
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
combine all of the like terms to get.....
6x-x-8x-2-3-4 = 0
-3x = 9(add/subtract the terms, and bring one onto the other side of the equationg)
x = -3 ( divide both sides by -3)
2006-11-14 15:42:06
·
answer #5
·
answered by D.P 3
·
0⤊
0⤋
x= -3
2006-11-14 15:46:54
·
answer #6
·
answered by Dome 1
·
0⤊
0⤋
x=-3
solution:
6x -3 -4 -8x = x +2
(-2x) - 7 = x + 2
x + 2x = -7 - 2
3 x = -9
x = -3
2006-11-14 15:41:47
·
answer #7
·
answered by orca1006 2
·
0⤊
0⤋
6x-3-4-8x=x+2
6x-8x-x=2+3+4
-3x=9
x=-9/3
x=-3
2006-11-14 15:41:33
·
answer #8
·
answered by -- 4
·
0⤊
0⤋
x= -3
6x-3-4-8x=x+2
-2x-7=x+2
-9=3x
-3=x
6(-3)-3-4-8(-3)=(-3)+2
-18-3-4+24=-3+2
-1=-1
2006-11-14 15:49:33
·
answer #9
·
answered by be wise 1
·
0⤊
0⤋
wellllllll first we have to simpify what we have -
your whole question did not make it
so far we have -7-2x=x+2
if that is it - add 2x to both sides
-7-2x+2x=x+2x+2
-7=3x+2.....subtract 2 from both sides
-7-2=3x+2-2
-9=3x
x= _________________ aHHHH YOU CAN DO THAT
2006-11-14 15:44:08
·
answer #10
·
answered by tomkat1528 5
·
1⤊
0⤋